2013
DOI: 10.12799/jkachn.2013.24.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Suicidal Ideation in People with Mental Disorder

Abstract: Purpose: This study was conducted to investigate factors influencing suicidal ideation in people with mental disorder. Methods: The subjects were 176 people with mental disorder from community mental health centers, social rehabilitation facilities, and university hospital psychiatric outpatient departments. The instruments used included a suicidal ideation questionnaire, a self-esteem scale, a spiritual well-being scale, a family support scale, and a professional support scale. Data were analyzed with t-test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
2
0
7
Order By: Relevance
“…This finding coincides with previous reports on the high rate of suicide attempts among PMDs and the prevalence of schizophrenia among PMDs who utilize CPRCs in Korea [ 5 - 8 ]. Families of middle-aged adults with mental disorders are exposed to extended periods of caregiving duties.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding coincides with previous reports on the high rate of suicide attempts among PMDs and the prevalence of schizophrenia among PMDs who utilize CPRCs in Korea [ 5 - 8 ]. Families of middle-aged adults with mental disorders are exposed to extended periods of caregiving duties.…”
Section: Discussionsupporting
confidence: 92%
“…A survey of all registered members of mental health institutes in Korea has revealed that more than half of all members (48,830 of 93,522) have severe mental disorders, namely, schizophrenia, major depressive disorder, and bipolar disorder [ 4 ]. Moreover, a survey of registered members with severe mental disorders in Seoul, Gyeonggi-do, Daegu, and Busan, Korea, found that 30%–40% of the members have a history of suicide attempts [ 5 - 8 ]. Protective factors for suicide among PMDs are currently under-researched in comparison to risk factors; individual therapy and family education appear to be the only intervention options available [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…또한, 군 입대 이후 자살 시도자의 31.3%는 정신질환 과 연관이 있었으며, 최근 1개월 이내에 정신질환을 진단받은 경우, 자살 위험은 약 15.0~29.8배까지 증가하였고, 입원 기간 동안 자살 사고가 있었던 경우 퇴원 후 자살로 1년 이내에 사망 군 자살은 군대 문제뿐 아니라 개인 심리적 및 사회적 요인 등이 복합적인 상호작용으로 발생하기 때문에 자살을 효과적 으로 예방하기 위해서는 자살과 관련된 위험 요인 뿐 아니라 보 호 요인을 다각적으로 파악할 필요가 있다[12,13]. 자살 관련 보호 요인은 자살의 고위험 상황에서 합리적으로 대처 또는 적응하여 자살을 막는데 기여할 수 있는 요인이다[14]. 즉, 자 는 신념, 가족에 대한 의식, 자살 자체에 대한 거부와 공포 등의 하위 개념이 포함되어 있다[19,24].…”
unclassified
“…심리사회적 요인으 로는 우울이 높을수록 [10], 자존감이 낮을수록 [10,11], 가족지 지가 낮을수록 [9], 스트레스가 높을수록 [11] 자살사고가 높았 다. 이들 정신장애에 포함된 정신과 진단명은 조현병, 우울증, 조울병, 분열형 정동장애 및 알코올 중독 등 다양하였다 [11,12]. 우리나라 정신건강증진센터에서는 등록된 회원의 대다 수는 조현병으로 진단된 대상자로 이들에게 사례관리 서비스 를 우선적으로 제공하고 있다 [13].…”
unclassified